O-035 Risk factors for delayed deterioration after cerebral venous thrombosis: a model to identify patients for early aggressive endovascular therapy. (23rd July 2017) - Bushnaq, S; Thacker, T; Abbas, M; Qeadan, F; Carlson, A
Abstract : Background: Cerebral venous thrombosis (CVT), including thrombosis of cerebral veins and dural sinuses is an unusual form of stroke. Anticoagulation remains the mainstay of treatment, with generally good results. A subset of patients however, may clinically or radiographically deteriorate despite anticoagulation, and in such cases, endovascular thrombolysis or thrombectomy is recommended. Early thrombectomy is technically more straightforward and so earlier identification of this high-risk group could potentially improve clinical outcomes in these patients. Methods: A retrospective chart review was performed on subjects with CVT from 01/2005 to 10/2016. Admission laboratory data including Complete Blood Count, Comprehensive Metabolic Panel, Liver Function Tests, and hypercoagulable labs were collected. Presenting symptoms, other potential risk factors, and location of thrombus were reviewed. The primary outcome was clinical deterioration, defined as symptomatic worsening due to CVT at follow up visits, death, repeat emergency room visits after discharge for CVT related complaints, or need for endovascular intervention. Bivariate analysis, multiple logistic regression modeling, and linear discriminant analysis were used to determine a predictive model for deterioration. Results: We identified 147 subjects with CVT. Headache was the most common symptomatology (66.67%), followed by nausea or vomiting (39.46%), focal weakness (33%), seizure (14.29%), and papilledema (10.88%). 15 (n=105, 74.47%) patients presented with a normal Glasgow coma scale (GCS). Hemorrhage on initial CT head was found in 54 patients (36.73%). The majority of patients were treated with anticoagulation (n=109, 75.69%). Out of 147 patients, 38 (25.85%) were found to have deterioration, 12 (8.33%) of whom underwent endovascular intervention. Risk factors on the bivariate analysis included decreased level of consciousness (Odds Ratio=5.76; 95% confidence interval, 2.59 to 12.77), papilledema (OR=4.522; 95% CI 1.55 to 13.18), seizure activity (OR=3.181; 95% CI 1.22 to 8.25), and bilateral tranverse sinus thrombosis (OR=3.448; 95% CI 1.25 to 9.48), (Figure 1). The final model included CVT location score (number of sinuses involved), oral contraceptive pills use, sodium level, platelet count, seizure activity on presentation, papilledema, and decreased level of consciousness on presentation. This model had 83.2 predictive ability to identify deterioration, sensitivity of 71.4 and specificity of 76.2 Conclusion: We found that decreased mental status, seizure activity, papilledema, number of involved sinuses, sodium level, and platelet level to be the most important factors in predicting deterioration after CVT. This group may represent a subset of patients in who early thrombectomy may be considered. Further prospective trials are needed to confirm this hypothesis. Disclosures: S. Bushnaq: None. T. Thacker: None. M. Abbas: None. F. Qeadan: None. A. Carlson: None.